Research on the Impact of Multi-Agent Information Traceability on Quality and Safety of Agricultural Product Supply Chain Under Blockchain - Fang, Lina; Zang, Xin (International Journal of Global Economics and Management, 2024)
With the increasing prominence of food safety problems, consumers are paying more and more attention to the quality and safety of agricultural products. Information traceability of agricultural products supply chain is an important way to ensure the quality and safety of agricultural products. Blockchain technology provides a new solution for information traceability of agricultural products supply chain with its characteristics of decentralization, immutable and transparency. This paper reviews the basic principles of blockchain technology and its application in agricultural supply chain information traceability. By combing relevant literature, it is found that blockchain technology is widely used in the production, processing, logistics and other aspects of agricultural products, effectively improving the transparency and traceability of the supply chain. Finally, it is concluded that the information traceability of agricultural product supply chain under the blockchain improves the traceability, visibility and information security of the supply chain, and also promotes the cooperation and coordination among various entities in the supply chain. With the continuous development and improvement of blockchain technology, its application in agricultural product supply chain information traceability will be more extensive and in-depth, providing more solid technical support for the quality and safety of agricultural products.